2006
DOI: 10.1074/jbc.m604477200
|View full text |Cite
|
Sign up to set email alerts
|

Broad Substrate Stereospecificity of the Mycobacterium tuberculosis 7-Keto-8-aminopelargonic Acid Synthase

Abstract: Biotin is an essential enzyme cofactor required for carboxylation and transcarboxylation reactions. The absence of the biotin biosynthesis pathway in humans suggests that it can be an attractive target for the development of novel drugs against a number of pathogens. 7-Keto-8-aminopelargonic acid (KAPA) synthase (EC 2.3.1.47), the enzyme catalyzing the first committed step in the biotin biosynthesis pathway, is believed to exhibit high substrate stereospecificity. Biotin (vitamin H) is an essential cofactor re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Thus we monitored the formation of the quinonoid intermediate I in the R. capsulatus ALAS-catalysed reaction using the substrate analogue O-methylglycine and transient kinetics under presteady-state conditions and following the changes in absorbance at 510 nm ( Figure 3 and Table 1). The observation of the quinonoid intermediate I in the R. capsulatus ALAS-catalysed reaction is in good agreement with similar results obtained from experiments performed with E. coli and Mycobacterium tuberculosis AONS [16,31] and SPT [32]. Similar to the reaction of the ALASglycine complex with succinyl-CoA, the kinetic trace for the reaction of the ALAS-O-methylglycine complex with succinyl-CoA was best described as a four-step process [eqn (1); k 1 = 2.96 s − 1 , k 2 = 0.19 s − 1 , k 3 = 32.10 s − 1 and k 4 = 0.64 s − 1 ; Table 1).…”
Section: Evidence For An α-Amino-β-oxoadipate Intermediate During Alasupporting
confidence: 89%
“…Thus we monitored the formation of the quinonoid intermediate I in the R. capsulatus ALAS-catalysed reaction using the substrate analogue O-methylglycine and transient kinetics under presteady-state conditions and following the changes in absorbance at 510 nm ( Figure 3 and Table 1). The observation of the quinonoid intermediate I in the R. capsulatus ALAS-catalysed reaction is in good agreement with similar results obtained from experiments performed with E. coli and Mycobacterium tuberculosis AONS [16,31] and SPT [32]. Similar to the reaction of the ALASglycine complex with succinyl-CoA, the kinetic trace for the reaction of the ALAS-O-methylglycine complex with succinyl-CoA was best described as a four-step process [eqn (1); k 1 = 2.96 s − 1 , k 2 = 0.19 s − 1 , k 3 = 32.10 s − 1 and k 4 = 0.64 s − 1 ; Table 1).…”
Section: Evidence For An α-Amino-β-oxoadipate Intermediate During Alasupporting
confidence: 89%
“…Research has discovered the complete biotin biosynthesis pathways in many different microbes, but the study on the biotin biosynthesis in M. tuberculosis is exiguous. Although the biotin synthesis genes in M. tuberculosis were deciphered [Cole et al, 1998;Camus et al, 2002] and some products of these genes were investigated [Bhor et al, 2006;Mann and Ploux, 2006], the process of biotin biosynthesis remains an unknown quantity.Biotin is unstable and spontaneously oxidizes to biotin sulfoxide. The Escherichia coli biotin d-sulfoxide reductase reduces biotin sulfoxide to biotin [del Campillo-Campbell and Campbell, 1982] and has essential role in assimilation of free oxidized methionines in E. coli [Ezraty et al, 2005].…”
mentioning
confidence: 99%
“…Recently, it was reported that Mycobacterium tuberculosis KAPA synthase shows a unique substrate stereospecificity: it uses both L-and D-alanine, 37) but the recombinant TTHA1582 protein did not utilize Dalanine.…”
Section: )mentioning
confidence: 99%